The Development of Comic Learning Media Featuring the Exemplary KH. A. Wahab Hasbullah to Improve Arabic Writing Skills - Maulidi; Mufidah, Milatul Laila; Rina Dian Rahmawati (UIN Syekh Wasil Kediri, Indonesia, 2024)
This study addresses the low Arabic writing skills of students at MAN 10 Jombang, attributed to a lack of engaging learning media. The aim is to develop a comic-based learning media themed on the exemplary life of KH. A Wahab Hasbullah to enhance students' motivation and writing skills. The research employs a Research & Development (R&D) methodology with both quantitative and qualitative approaches. The comic's development involved expert validation, individual trials, small-scale tests, and field testing. The results show a significant improvement in Arabic writing skills, with an average pre-test score of 57.5 and a post-test score of 85.75. The conclusion is that comics are effective as learning media, capable of enhancing students' writing skills and learning interest. It is recommended to expand the use of comics across various subjects and integrate exemplary values to improve students' character education.